Studies toward the total synthesis of naturally occurring pyranonaphthoquinones from ventilago harmandiana - Sopanat Kongsriprapan (2018)
The enantioselective synthesis of a naturally occurring pyranonaphthoquinone isolated from a Thai endemic plant, Ventilago harmandiana, has been achieved. L-Rhamnose and gallic acid were used as the starting materials. A new C-1-glycosidation of L-rhamnal with trimethyl aluminum in the presence of a catalytic amount of ytterbium(III) triflate was developed. A new reagent, PhSCF 2 H/SnCl 4 , for the formylation of partially deactivated and hindered aromatic compounds has been introduced. Phenylthiophthalide was used efficiently as a cycloannulating agent in the Hauser cycloannulation reaction, employing slightly excess lithium t-butoxide as a base with a catalytic amount of lithium chloride. The synthetic route developed is applicable for the synthesis of other analogues with substituents at the aromatic and pyran rings. © 2012, IUPAC.